1997
DOI: 10.1002/j.1477-8696.1997.tb06244.x
|View full text |Cite
|
Sign up to set email alerts
|

Large rotating ice discs on ice‐covered rivers

Abstract: The bolometer and radiant energy. h c. Am. Acad. Arts Sci., 16, pp. 342-358-(1883) The selective absorption of solar energy. Am. 3. Sci., 25, pp. 169-196-(1884) Researches on solar heat and its absorption by the Earth's atmosphere (Report of the Mount Whimey Expedition). h$ Pap. Signal Sew., 15, pp. 11, 42, United States War Department, Washington-(1885) Observations on invisible heat and the recognition of hitherto unmeasured wavelengths , made at the Allegheny Observatory. h c. Am. SOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Large floating ice blocks have been observed on frozen rivers [1][2][3][4]. This pretty rare phenomenon is shown during winter news broadcasts on TV as the disks surprisingly rotate [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large floating ice blocks have been observed on frozen rivers [1][2][3][4]. This pretty rare phenomenon is shown during winter news broadcasts on TV as the disks surprisingly rotate [5].…”
Section: Introductionmentioning
confidence: 99%
“…This pretty rare phenomenon is shown during winter news broadcasts on TV as the disks surprisingly rotate [5]. In a paper of 1997, Nordell et al reported several events of rotating ice disks [1]. The diameter D of the disks has been observed to range over two orders of magnitude from 1 to 100 m. On the other hand, the rotation speeds do not seem to depend on the size of the disk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pretty rare phenomenon can be observed during winter news broadcast as the discs surprisingly rotate. In a paper of 1993, Nordell et al reported several events of rotating ice discs [1]. The Table I presents the diameters D, the rotating speed w expressed in degrees per second for different observations (place, date and references are indicated).…”
Section: Introductionmentioning
confidence: 99%
“…A rare natural phenomenon, a large circular rotating ice disc in a slightly larger hole in the ice cover, occurs infrequently in some rivers in cold regions. An illustration of a revolving ice cake on the Mianus River, USA, was published in 1995(Scientific Amen'can 1995. Photographs of such discs, on the Nidelva River in Norway and Rancho Nuevo Creek in the USA, were published in La HoudZe Blanche (1971) and EOS (1983) respectively.…”
mentioning
confidence: 99%